The witches of El Paso - Jaramillo, Luis (Atria Books, 2024)
"A riveting multigenerational tale of magic, sisterhood, and borders spanning centuries--from modern-day El Paso, to the 1940s, to 18th century colonial Mexico. It's 1943 in El Paso, Texas, and 18-year-old Nena spends her days caring for the infant children of her older sisters, while longing for a life of adventure and purpose. She also has a secret: her vivid premonitions are what's causing her to faint, and she fears she'll end up like the scary old curandera who lives down the street. When the mysterious and stern Sister Benedicta arrives late one evening, Nena is taken across borders of space and time for a life-changing experience in colonial Mexico. In the present-day, Nena's grand-niece Marta is balancing motherhood and a struggling legal aid practice, just as her own supernatural powers are emerging. When the 93-year-old Nena's care is added to Marta's already full plate, the two women's destinies become irrevocably intertwined, as they both struggle to find fulfillment and escape through La Vista, or "the hum," a mysterious, inherited magical ability that allows its recipients to tap into the subconscious hunger for destruction, rebirth, the natural world, lust, and the call to heed our darkest desires and brightest truths. Blending historical fiction with magical realism, The Witches of El Paso explores the enticing and destructive magic that arises out of the depths of human desire, to tell a story of empowerment and wonder that transcends borders both physical and metaphorical"--